Sustainable Halal Value Chain performance for MSMEs: the roles of digital technology, R&D, financing, and regulation as antecedents - Budi Harsanto; Mahir Pradana; Egi Arvian Firmansyah; Ardi Apriliadi; Joval Ifghaniyafi Farras (Cogent Business & Management, 2024)
This article aims to provide a comprehensive and trustworthy HVC model for Micro, Small, and Medium-Sized Enterprises (MSMEs) by considering the role of digital technologies, legislation, finance, and research and development. To give a comprehensive understanding of the subject matter, we employed quantitative research methods. We used a sample based on the database of The Halal Product Assurance Organizing Body (BPJPH) to collect data from 278 respondents. Our respondents are located in thirteen different Indonesian cities who run MSMEs and from various backgrounds, such as practitioners, associations, legislators, academics, and other pertinent stakeholders. According to our findings, research and development have a negligible impact on halal chain performance, while halal value chain elements have a considerable impact. Previous HVC research has primarily been descriptive, characterizing situations or concepts or reviewing literature, with little empirical assessment of the relationship between significant halal value chain aspects and value chain performance. Our research contributes in filling this gap.
Keywords: D13; I31; J22; K31; 650; Halal Value chain; halal logistics; value chain; Islamic business; MSME